2022
DOI: 10.1007/s10965-022-03135-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of wet adhesives based on (poly (vinyl butyral-co-vinyl alcohol-co-vinyl acetate)/castor oil/styrene butadiene rubber) using gamma irradiation for trapping of reptiles and rodents

Abstract: Wet adhesives from poly (vinyl butyral-co-vinyl alcohol-co-vinyl acetate), castor oil, and styrene butadiene rubber were prepared at variable compositions. These components were exposed to a certain range of irradiation dose for γ-rays. Wet adhesives were characterized by adhesion force, Fourier transform infrared, thermogravimetric analysis and derivative thermal gravimetric, gel permeation chromatography, proton nuclear magnetic resonance spectroscopy and scan electron microscopy. Results declared that dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…26 Zhang et al found that a series of polar groups were formed and grafted on the fiber to induce an evolution of the surface. Awadallah-F et al 27 modified wet adhesive by using γirradiation, and they found that γ-rays could induce the graft copolymerization reaction to take place on the backbone of styrene butadiene rubber and poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), which could ameliorate the adhesion and thermostability of wet adhesives. Zhou et al 28 used γ-rays to enhance the ceramic yield.…”
Section: Introductionmentioning
confidence: 99%
“…26 Zhang et al found that a series of polar groups were formed and grafted on the fiber to induce an evolution of the surface. Awadallah-F et al 27 modified wet adhesive by using γirradiation, and they found that γ-rays could induce the graft copolymerization reaction to take place on the backbone of styrene butadiene rubber and poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), which could ameliorate the adhesion and thermostability of wet adhesives. Zhou et al 28 used γ-rays to enhance the ceramic yield.…”
Section: Introductionmentioning
confidence: 99%